RELATIONS DIETARY AND GENDER WITH NUTRITIONAL STATUS OF CHILDREN IN SDN 43 KOTA PEKANBARU - Anita, Wan (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Nutritional status is the state of the body as a result of food consumption and the use of nutrients. Differentiated between malnutrition status, less, good and more.Status malnutrition, less or more will occur nutritional disorders. Factors that affect the fulfillment of nutritional needs of school children are age, physical activity, attitudes toward food and do not like nutritious foods. The purpose of the study to determine the relationship between diet and sex with nutritional status of children. The research design is a quantitative analitical with cross sectional approach. The research was conducted in SDN 43 Kota Pekanbaru The sample of this research is elementary school children of Class IV, V and VI which amounted to 131 respondents. Data collection using questionnaires and nutritional status based on IMT / U standard. There is relationship between diet with child nutrition status with p value = 0,00 and relationship between sex with child nutritional status with p value = 0,038. Expected increase in health promotion activities, especially the importance of diet and nutritional needs are good in improving the nutritional status of school children through counseling. Provide counseling about the importance of nutritional needs in girls by changing behavior patterns in consuming food.Status gizi adalah keadaan tubuh sebagai akibat konsumsi makanan dan penggunaan zat-zat gizi. Dibedakan antara status gizi buruk, kurang, baik dan lebih.Status gizi buruk, kurang maupun lebih akan terjadi gangguan gizi. Faktor yang mempengaruhi pemenuhan kebutuhan gizi anak sekolah adalah usia, aktifitas fisik, sikap terhadap makanan dan tidak suka makanan-makanan bergizi. Tujuan penelitian untuk mengetahui hubungan pola makan dan jenis kelamin dengan status gizi anak. Desain penelitian adalah analitik kuantitatif dengan pendekatan cross sectional. Penelitian dilakukan di SDN 43 Kota PekanbaruÂ Sampel penelitian adalah anak SD Kelas IV, V dan VI yang berjumlah 131 responden. Pengumpulan data menggunakan kuisioner danÂ status gizi berdasarkan standar IMT/U. Terdapat hubungan antara pola makan dengan status gizi anak dengan p value =0,00 dan hubungan antara jenis kelamin dengan status gizi anak dengan p value =0,038. Diharapkan peningkatan kegiatan promosi kesehatan terutama pentingnya pola makan dan kebutuhan gizi yang baik dalam meningkatkan status gizi anak sekolah melalui penyuluhan. Memberikan penyuluhan tentang pentingnya kebutuhan nutrisi pada anak perempuan dengan merubah pola perilaku dalam mengkonsumsi makanan.